Analysing gene expression : a handbook of methods : possibilities and pitfalls - Lorkowski, Stefan; Cullen, Paul (Wiley-VCH, 2003)
This book combines the experience of 225 experts on 900 pages. Scientists worldwide are currently overwhelmed by the ever-increasing number and diversity of genome projects. This handbook is your guide through the jungle of new methods and techniques available to analyse gene expression - the first to provide such a broad view of the measurement of mRNA and protein expression in vitro, in situ and even in vivo. Despite this broad approach, detail is sufficient for you to grasp the principles behind each method. In each case, the authors weigh up the advantages and disadvantages, paying particular attention to the automated, high-throughput processing demanded by the biotech industry. Completely up to date, the book covers such ground-breaking methods such as DNA microarrays, serial analysis of gene expression, differential display, and identification of open reading frame expressed sequence tags. All the methods and necessary equipment are presented visually in more than 300 mainly colour illustrations to assist their step-by-step reproduction in your laboratory. Each chapter is rounded off with its own set of extensive references that provide access to detailed experimental protocols. In short, the bible of analysing gene expression.
Keywords: Gene Expression; Reference Books, Medical; exprese genu; příručky lékařské; genetika, lékařská genetika